Dorsal Island Penile Fasciocutaneous Flap for Fossa Navicularis and Meatal Strictures: Short and Intermediate Term Outcome in West African Men - Tijani, Kehinde Habeeb; Ojewola, Rufus Wale; Odusanya, Benjamin; Yahya, Ganiyu Lanre (Urology Journal, 2015)
Purpose: The aim of this study was to evaluate the use of a dorsal island penile fasciocutaneous flap in the management of resistant fossa navicularis strictures in circumcised West African men. Materials and Methods:From January 2004 to December 2013 there were twenty-one patients with fossa navicularis strictures (FNS) with or without meatal stenosis who underwent urethroplasty using a previously described technique and a dorsal island penile fasciocutaneous flap. The average patient follow-up was 25.9 months. Results: Urethral catheterization was the most common cause of FNS. All of the patients had successful urethral function and acceptable cosmetic results. One patient had partial dorsolateral skin necrosis that healed with conservative measures. All patients, including the five patients with meatal stenosis,retained the natural shape of the external meatus and hada natural urine stream. Conclusion:The penile cap technique uses a dorsal island fasciocutaneous flap and provides satisfactory functional and cosmetic outcomes in the management of fossa navicularis and meatal strictures.